Modelling the impact of climate change risk on bioethanol supply chains - (:unkn) unknown (ELSEVIER SCIENCE INC, 2020)
The availability of bioethanol, a promising renewable alternative to fossil fuels depends on the supply of biomass produced from agricultural resources. The study attempts a system dynamics modelling approach to explore the implications of greenhouse gas concentration trajectories associated with climate change on bioethanol supply chains. Eight different climate change scenarios are simulated spanning over a 40-year horizon to predict biomass yield and bioethanol availability, by considering first generation (corn) and second generation (switchgrass) ethanol feedstocks. The developed model is used to assess the extent of potential disruptions resulting from global warming. Cascading effect of climate change risk is evident through decreased yield and production, and increased shortages at end customer in the bioethanol supply network. The results indicate that, if climate change risk is not adequately mitigated and current used source of ethanol (corn) continues to be leveraged, the bioethanol availability may decrease by one-fourth by the year 2060. The comparative study encourages exploring the increased use of switchgrass as a sustainable feedstock for renewable energy. Developed insights support identifying effective climate change mitigation policies and sustainable investment decisions for the reduction in carbon emissions.
Keywords: Bioethanol; Climate change; Renewable energy; Supply chain risk; System dynamics; LOGISTICS ISSUES; WASTE-WATER; BIO-ENERGY; BIOMASS; DESIGN; OPTIMIZATION; MANAGEMENT; FOOD; YIELD; CHALLENGES